(untitled) (Nóema, 2022)
Starting from the thesis that in neoliberalism a practice of government of others is at work and it is carried out through the solicitation of a particular way of government of oneself, in this contribution we will try to consider the specific regime of truth that emerges in relation to this form of exercise of power. To understand this declination of veridiction as a technique of the self capable of ensuring the government of others, this paper will be developed in three parts. At first, an attempt will be made to define the notion of a regime of truth so that we can understand its significance in relation to neoliberal governmentality. In this way it will be possible, at a later stage, to analyze the neoliberal regime of truth by defining its functioning and its targets. We will consider, finally, the effects that these veridictional practices generate in the processes of subjectivation to the extent that they produce the individual as an entrepreneur of oneself, whose choices and behaviors have to be guided by the logic of human capital.